2004
DOI: 10.1038/sj.leu.2403234
|View full text |Cite
|
Sign up to set email alerts
|

Acute promyelocytic leukemia: where does it stem from?

Abstract: A fundamental issue in cancer biology is the identification of the target cell in which the causative molecular lesion arises. Acute myeloid leukemia (AML) is thought to reflect the transformation of a primitive stem cell compartment. The resultant 'cancer stem cells' comprise only a minor portion of the leukemic clone but give rise through differentiation to more committed progenitors as well as differentiated blasts that constitute the bulk of the tumor. The maintenance of the leukemic clone is dependent on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 79 publications
2
64
0
Order By: Relevance
“…5,6 Indeed, injection of these cells into immunocompromised nonobese diabetic/severe-combined immunodeficient (NOD/SCID) mice leads to a disease with phenotypic and molecular characteristics of human AML. Over the last few years, remarkable progress has been made in the elucidation of the molecular pathogenesis of AML.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Indeed, injection of these cells into immunocompromised nonobese diabetic/severe-combined immunodeficient (NOD/SCID) mice leads to a disease with phenotypic and molecular characteristics of human AML. Over the last few years, remarkable progress has been made in the elucidation of the molecular pathogenesis of AML.…”
Section: Introductionmentioning
confidence: 99%
“…44 Evidence for the progenitor model Combined evidence from mouse models for APL using differentiation stage-specific promoters and transplantation of APL samples into NOD/SCID mice has led to the theory that a committed progenitor is the target of the translocation. This theory has been the subject of a recent review 76 The MLL-Gas7 translocation induced a mixed lineage leukemia (MLL) when the fusion protein was expressed in MPPs whereas it only induced a lymphoid or myeloid malignancy when expressed in either a CLP or CMP, which would argue in favor of the progenitor model. 81 Similarly, phenotypically identical AML was obtained when the MLL-ENL fusion protein was expressed selectively in either hematopoietic stem cells, CMPs or GMPs, also arguing in favor of the progenitor model.…”
Section: Evidence For the Stem Cell Model In Amlmentioning
confidence: 99%
“…[74][75][76] When Bonnet et al 77 enriched for CD34 þ /CD38À cells from AML samples, they were able to induce a leukemia in NOD/SCID mice with much fewer cells, arguing that the leukemic stem cell has very similar properties like the hematopoietic stem cell (HSC). 77 Lessard and Sauvageau 78 and Clarke et al 79 have shown the requirement of a gene called BMI-1 for the proliferative capacity of normal and leukemic stem cells.…”
Section: Evidence For the Stem Cell Model In Amlmentioning
confidence: 99%
“…11,12 From the arguments reported above, it could seem that APL exhibits a univocal immunophenotype, without exceptions and shades. Actually, flow cytometry enables to detect some divergent behaviors from deep-rooted rules.…”
Section: The Search For Apl Leukemic Stem Cellsmentioning
confidence: 99%
“…By contrast, other experiments demonstrated the presence of the PML-RARa within the majority of cells located in the CD34 þ CD38À fraction, especially in cases of hypogranular variant APL. 11 Edwards et al 13 demonstrated, by using a fluorescence-activated cell sorter and fluorescence in situ hybridization (FISH) approach, the presence of t(15;17) and PML/RARa fusion gene within both primitive CD34 þ CD38À and committed CD34 þ CD38 þ progenitor cell sub-populations.…”
Section: The Search For Apl Leukemic Stem Cellsmentioning
confidence: 99%